Fractional calculus of variations for double integrals - Odzijewicz, T. (2011)
We consider fractional isoperimetric problems of calculus of variations with double integrals via the recent modified Riemann-Liouville approach. A necessary optimality condition of Euler-Lagrange type, in the form of a multitime fractional PDE, is proved, as well as a sufficient condition and fractional natural boundary conditions. © Balkan Society of Geometers, Geometry Balkan Press 2011.